Methane and non-methane organic compounds oxidation in landfill bio-covers - Albanna, Muna (University of Ottawa (Canada), 2009)
One critical source, which adds to the anthropogenic methane (CH 4) emissions, is solid waste disposal. The biogas generated from biodegradation of solid waste in landfills, known as landfill gas (LFG), consists of CH 4, carbon dioxide (CO2), plus trace amounts of non-methane organic compounds (NMOCs). Most of the existing landfills around the world do not have LFG collection setups, and the emissions are just released into the atmosphere. Oxidation of CH4 and NMOCs by methanotrophic bacteria within the landfill cover (LFC) provides a sink for these harmful fugitive emissions. The scope of this research was to carry out a comprehensive study on the biological oxidation of CH4 and NMOCs in the LFC, under diverse operating conditions. To achieve this goal, various parameters affecting the oxidation process, including cover medium, temperature, saturation limit and nutrients addition, were studied. Statistical analysis and modeling were carried out to estimate the interactions between several parameters under investigation, and to draw conclusions about the combined effects of these parameters on the LFC system. The effects of NMOCs on CH4 oxidation capacity of the LFC were examined in batch scale and continuous flow column experiments. Additionally, the co-metabolic abilities of methanotrophs were explored and the biological bio-degradation rates on NMOCs were estimated under different temperature and moisture content levels. Artificial neural networks (ANN) modeling technique was used to describe the complex input/output relationships and to simulate the CH4 oxidation rates in the presence of NMOCs under diverse conditions that are representative of LFC system.
Keywords: Engineering, Environmental.